Trends and Research Directions of Human Capital in the Public Sector: A Bibliometric Analysis - Azzara, Annisa Renanthera; Robert Simbolon; Hartati, Sri; Muhamad Takiyuddin Ismail (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2025)
Human resources are critical factor that drives the competitiveness of public sector organizations to achieve better performance. This study aims to  map the evolution of research on human capital in  the context of human resources in the public sector by using bibliometric analysis. Data were retrieved from Scopus database covering the period 1966 to 2025 with a research sample of 2.034 journal publications according to the selected keywords.  The search strategy combined two sets of keywords: “human capital” OR “human capital development” OR “workforce management” and “public sector” OR “public administration” OR “government” OR “civil service” OR “public organization”, applied to titles, abstracts, and keywords (TITLE-ABS-KEY). The final dataset, consisting of journal articles in English and indexed in relevant subject areas such as social sciences was analyzed using VOSviewer software. The analysis identified research trends, author productivity, institutional and country contributions, keyword co-occurrence clusters, and future research directions. This study contributes by providing a systematic mapping of human capital research in the public sector, highlighting both the progress achieved and the gaps that remain for further exploration. The authors conclude that it is important to increase public organizations awareness of the role of human resources and human capital investment with the development and management of human resources, and that there is a need for the development of research themes to broaden insights and update the literature in the future.